O papel do CaO do resíduo de concha de marisco (mytella charruana) calcinada no sistema caulim-feldspato-quartzo - cerâmica dentária - Dias, Rafael Leandro (Universidade Federal Rural do Semi-Árido, 2018)
A lot of waste is generated by the population annually in the environment we live in and are disposed of or reused in various ways, not being very different in the seas where small amounts of seafood shells are also discarded brought to the beaches, but loads of waste shells is produced resulting from fishing / collection of seafood restaurants. This study aims at the possibility of partial replacement of feldspar ceramic bodies by clamshell powder, because they are natural sources of calcium, adding value to waste. The study also seeks to encourage technological innovation through the use of waste materials to human prosthesis once it occurs the inert mineral natural contaminants.
Monografia
Keywords: Porcelana dentária; Sustentabilidade; Resíduo sólido; Conchas de marisco; Reaproveitamento; Dental porcelain; Sustainability; Solid waste; Seafood shells; Reuse; ENGENHARIAS::ENGENHARIA MECANICA